Tidal stream resource assessment in the Dover Strait (eastern English Channel). (December 2016) - Thiébaut, Maxime; Sentchev, Alexei
Highlights: Tidal stream resource variability in the Dover Strait was characterized and mapped by using velocity time series recorded by VHF radars and by ADCP. The most energetic area was found west of the Cape Gris Nez with the time mean velocity of 1 m/s and spring tide velocity of 1.4 m/s. In this sector, the mean power density in the surface layer attains 0.9 kW/m 2 and 2.2 kW/m 2 during spring tide. The power density is found three times lower in the bottom layer. Abstract: A methodology of tidal flow resource assessment in the Dover Strait is presented. The resource assessment is performed using surface velocity time series recorded by Very High Frequency Radars (VHFR) and ADCP velocity measurements. Following the EMEC guideline, the major parameters of tidal flow conventionally used for tidal energy site screening are estimated and mapped. The combination of two sources of data allowed to characterize the current velocity variation in three spatial dimensions and in time, which increased confidence in hydrokinetic resource assessment from the radar data. Current velocities provided by the radars show strong spatial variation and fortnightly modulation. The most energetic area was found west of the Cape Gris Nez with the peak velocity of 2.5 m/s, mean velocity of 1 m/s, and spring tide average velocity of 1.4 m/s. Velocities exceeding 1 m/s are observed more than 50% of time there. Averaged velocity profiles derived from ADCP data were obtained for different stages of the tidal cycle and then approximated by a power law function. Using velocity time series provided by the radars and the power law velocity profiles, the power density time series in the surface and bottom layers were generated. The analysis of these data show that west of the Cape Gris Nez, the mean power density attains its maximum value 0.9 kW/m 2 in the surface layer and a peak value 5 kW/m 2 . In the rest of the domain, the mean power density varies from 0.1 to 0.6 kW/m 2 . The power density is found three times lower in the bottom layer. A three dimensional hydrodynamic model MARS-3D is used for comparison with experimental data. The model results are in good agreement with observations thus allowing the use of the model for assessing tidal stream resource in extended area.